Enhancement Efficiency of Organic Photovoltaic Cells via Green Solvents and Nontoxic Halogen‐Free Additives. (12th September 2021) - Fu, Zhijie; Liu, Xingpeng; Niu, Xixi; Ren, Meiling; Xue, Luyang; Du, Sanshan; Tong, Junfeng; Li, Jianfeng; Bao, Xichang; Xia, Yangjun
Abstract: For organic photovoltaic cells, the development of new green solvents and nontoxic and halogen‐free additives is an urgent issue. Here, a simple combination of o ‐xylene (O‐XY) and ethyl 2‐hydroxybenzoate (EHB) is introduced in inverted devices based on poly[4, 8‐bis(5‐(2‐ethylhexyl)‐thiophene‐2‐yl) benzo[1, 2‐b;4, 5‐b′] dithiophene‐2, 6‐diyl‐alt‐(4‐(2‐ethylhexyl)‐3‐fluorothieno[3, 4‐b] thiophene)‐2‐carboxylate‐2‐6‐diyl]:[6, 6]‐phenyl‐C71 ‐butyric acid methyl ester (PTB7‐Th:PC71 BM) as blend layers, the device performance reaches optimal values (9.29%) when O‐XY and 3% EHB are introduced as additives, accompanied by the maximum fill factor (67.5%) and J SC (17.20 mA cm −2 ). From the results of characterization analysis, it is clear that EHB additive improves the crystallinity of the donor by regulating the kinetic process of active layer formation, selectively solubilizes the more aggregated fullerene acceptors, which allows PTB7‐Th to enter the conformational domain of PC71 BM, and accelerates the molecular rearrangement. Besides, the EHB additive not only reduces the recombination, increases the carrier migration rate but also promotes the crystallinity of the donor, resulting in a tighter stacking. This work provides a green combination of solvents and additives that is important for the mass production of solar cells. Abstract : A nontoxic green additive (ethyl 2‐hydroxybenzoate) and o ‐xylene solvent‐based processing system is demonstrated and it yields even better organic photovoltaic device morphology and performance than that obtainable with conventional halogenated solvents.